(untitled) (East West Medical College Journal, 2026)
Background: Subaxial cervical spine (from cervical 3rd to 7th vertebral level) injury has a catastrophic impact over patient’s quality of life, personal, social, psychosocial and financial aspect with potentially devastating outcomes. Several factors play role in the management, evaluation, surgical decision-making process, improved outcome and prognosis of these patients. But which factors determine outcome significantly is still a topic of debate. Objective: The purpose of this study was to analyze and evaluate the factors influencing neurological outcome of subaxial cervical spine injury following surgical intervention. Materials and method: This prospective observational study was conducted among 27 Patients with traumatic subaxial cervical spine injury in the Department of Neurosurgery, Chittagong Medical College and Hospital, Chattogram. Demographic factors such as age, gender, etiology of injury, preoperative American Spinal Injury Association (ASIA) grade, C3-C4 versus C5-C7 cervical level of injury, radiological factors on Magnetic Resonance Imaging (MRI), and timing of intervention were studied. Change in the neurological status by one or more ASIA grade from the date of admission to 6 months follow-up was taken as an improvement. Functional grading was assessed using the Functional Independence Measure (FIM) score at 6 months follow-up. Results: Out of 27 analyzed cases all were male except one with most of the patients was in the age group of 21-30 years. Fall of heavy objects over head was the most common injury (44.4%) followed by fall from height (25.9%). 5 (18.5%) patients were expired during 6 months period. One, two and three grade improvement in ASIA grade was observed respectively in 55.6%, 22.2% and 3.7% patients. A total of 22 patients were categorized into the improved group and 5 patients into the not improved group. Age, sex, preoperative clinical and radiological features were not significantly different between these two groups. Maximum improvement in average FIM score was noted in ASIA grade C, with improvement in average scores from 81.50 to 110.75. Patients with preoperative Maximum Spinal Cord Compression (MSCC) ≤30% and edema in ≤3 segments of the spinal cord had significantly higher mean FIM scores than their counterpart. Conclusion: Maximum spinal cord compression and level of edema in MRI werethe two significant factors for improved neurological outcome after 6 months follow-up, in patients with traumatic subaxial cervical spine injury. EWMCJ Vol. 14, No. 2, July 2026: 106-115